Analysis Of The Determinants Of Msme Development In Besitang District - Barus, Muhammad Arif; Nasution, Muhammad Lathief Ilhamy; Tambunan, Khairina (Universitas Trunodjoyo Madura, 2025)
This study aims to analyze the influence of trust, working capital, market aspects, and sharia compliance on the development of micro, small, and medium enterprises (MSMEs) in Besitang Regency. MSMEs are a sector that has a strategic role in driving economic growth, but often faces various obstacles in its development. Using a quantitative approach, data were collected through questionnaires distributed to MSME actors in the area. The analysis technique used includes multiple linear regression to determine the relationship between independent variables (trust, working capital, market aspects, and sharia compliance) to the dependent variable (MSME development). The data analysis tools used are the classical assumption method, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that: (1) Trust does not have a significant effect on the development of MSMEs in Besitang Regency, indicated by the trust coefficient value (X1) which is positive (0.066) and the p value is smaller than the significance level (0.623 0.05) and the calculated t (0.439) t table (2.368). (2) Working capital does not have a significant effect on the development of MSMEs in Besitang District, indicated by the working capital coefficient value (X2) which is positive (0.011) and the p value is smaller than the significance level (0.909 0.05) and the calculated t (0.115) t table (2.368). (3) Market access has a significant effect on the development of MSMEs in Besitang District, indicated by the Market Access coefficient value (X3) which is positive (0.442) and the p value is smaller than the significance level (0.001 0.05) and the calculated t (3.983) t table (2.368). (4) Sharia compliance does not have a significant effect on the development of MSMEs in Besitang District, indicated by the positive value of the sharia compliance coefficient (X4) (0.107) and the p-value is smaller than the significance level (0.1139 0.05) and the calculated t value (1.139) t table (2.368). (5) Trust, working capital, market access and sharia compliance have a significant effect on the development of MSMEs in Besitang District, indicated by the p-value is smaller than the significance level (0.002 0.05) and the calculated f value (4.587) ft table (2.47). and the determination coefficient (R2) value is 0.132 or 13.2%. This value shows that 13.2% of MSME development is influenced by trust, working capital, market access and sharia compliance. while the remaining 86.8% is influenced by independent variables that were not studied.Keywords: Trust, Working Capital, Market Aspect, Shariah Compliance, MSME Development